PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS ETNOMATEMATIKA PADA MOTIF BATIK LOKATMALA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Sulaeman, Nurmala Putri; Mulyanti, Yanti; Setiani, Ana (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This purpose of this study is to evaluate the validity, practicality, and effectiveness of Ethnomathematics-based digital teaching materials on Lokatmala Batik Motifs to Improve Mathematical Problem-Solving Ability. This research use the (RD) methode wuth the ADDIE model. Data collection techniques were carried out through interviews, questionnaires, and tests. The research test subject is VII grade students of MTs-Huseiniyah. The results of the analysis show that the teaching materials developed have a validity score of 93% (very valid), practicality of 82% (efficient), and effectiveness of 0.50 (effective). So it is inferred that the ethnomathematics-based digital teaching materials on lokatmala batik developed are valid, useful, and effective in improving the ability to solve mathematical problems